2003
DOI: 10.1177/1359105303008001434
|View full text |Cite
|
Sign up to set email alerts
|

Development of Review Criteria to Evaluate Health Behavior Change Websites

Abstract: A growing number of major health care organizations, such as the American Heart Association and the Mayo Clinic, are investing considerable resources in developing and marketing Internet-based programs for health promotion and disease management. These programs have the potential to provide some of the best-tailored interventions in behavior change science at relatively low costs. This report discusses review criteria developed in order to conduct a systematic evaluation of Internet programs for preventive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 2 publications
0
36
0
Order By: Relevance
“…Attention, therefore, should be placed on the interactive and counseling aspects of web-based interventions. Perhaps if future studies include web-based health resources criteria for evaluating the quality of Internet health programs [26], the efficacy of these interventions can be improved.…”
Section: Discussionmentioning
confidence: 98%
“…Attention, therefore, should be placed on the interactive and counseling aspects of web-based interventions. Perhaps if future studies include web-based health resources criteria for evaluating the quality of Internet health programs [26], the efficacy of these interventions can be improved.…”
Section: Discussionmentioning
confidence: 98%
“…These personality characteristics could be used to match interventions to individuals, thereby providing a closer link between intervention message and purpose, and the characteristics of the person receiving the intervention. In today's fast-growing technological world, the development of interventions that are computer-tailored in real time to address the characteristics of individual recipients is feasible, and is being used in an increasing number of settings and to address many different behaviors (Ausems et al, 2002;Carlson et al, 2000;August et al, 2001;Chiauzzi et al, 2005;Cummins et al, 2003;Werch, 2001;Werch et al, 2005). This approach may also show promise for tailoring driving safety interventions to individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women have specifically requested current evidence-based recommendations for physical activity to help them to be more active [22]. However, studies have suggested that women may not know how to evaluate the accuracy of the information they receive and do not consistently check the source of information [26,27]. Recent theories posit that improving the quality and precision of information about physical activity may be insufficient to change this behavior; the timing and Policy: Health care providers could easily, with little resources (i.e., time, money) use Text4baby to refer patients to evidence-based information about physical activity during and after pregnancy.…”
Section: Introductionmentioning
confidence: 99%